UPAYA PEMBERDAYAAN KADER POSYANDU LANSIA TENTANG DETEKSI DEPRESI LANSIA - Atiek Murharyati; Yunita Wulandari; Wahyuningsih Safitri (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2020)
to invite people to take part in activities at Posyandu. Hypertension is a big problem for the elderly in every elderly posyandu in Indonesia. One of the risk factors for hypertension is stress. Psychosocial changes that occur in old age due to cognitive changes, disease conditions, loss of social roles also affect the self-concept of the elderly and can become stressors, making them prone to experiencing common psychological problems, namely depression. Depression in the elderly can be reduced in several ways, one of which is the spiritual guidance approach. The purpose of this community service implementation is that elderly posyandu cadres in DusunNgangkruk RT 01 RW 14 Kelurahan Selokaton can understand how to detect depression in the elderly. The methods used are lectures, demonstrations and question and answer. The results of the implementation of community service regarding balanced nutrition in toddlers showed that mothers of toddlers became more aware of the Empowerment of Elderly Posyandu Cadres about Elderly Depression Detection with an average knowledge value of Elderly Depression Detection with a percentage of 80%. The conclusion from this community service is that the lanisa cadre is important to understand early detection of depression in the elderly because it can improve the health status of the elderly.